Integrative GWAS and RNA-Seq analysis for target identification and virtual drug screening in colorectal cancer - Qinghui Liu; Yiyang Lei; Zixuan Liu; Jiale Han (PLoS ONE, 2025)
Background Colorectal cancer (CRC) is a leading cause of global cancer-related mortality, necessitating the identification of novel therapeutic targets. Integrating genetic and transcriptomic data may reveal key molecular drivers of CRC progression and treatment opportunities. Methods We performed a multiomics analysis combining genome-wide association study (GWAS) data (p < 1e-6) and RNA-seq data from the TCGA. Differential expression analysis (Limma) identified 24 consistently dysregulated genes (17 mRNAs, 7 lncRNAs) in CRC. Survival analysis was used to evaluate their prognostic impact on overall survival (OS), relapse-free survival (RFS), and post progression survival (PPS). Drug‒gene interactions were explored via Enrichr, and virtual screening (PubChem) prioritized high-affinity compounds that target PYGL, a metabolic regulator. Results Integration of GWAS and RNA-seq revealed that 24 CRC-associated genes, including PYGL , SMAD7 , and TCF7L2 , are involved in tumor metabolism and Wnt/TCF signaling. Survival analysis revealed that five genes ( CDKN2B , BOC , METRNL , etc.) were significantly correlated with OS, RFS, and PPS. Ten small-molecule candidates targeting PYGL exhibited high binding affinity, suggesting their therapeutic potential. Conclusion This study identified CRC-linked genes through GWASs and transcriptomics, highlighting their prognostic and druggable relevance. Computational drug repurposing pinpoints PYGL inhibitors as promising candidates, offering a translational framework for CRC therapy development.